COVID-19 MISINFORMATION: HOW DOES SCIENTIFIC INFORMATION LITERACY PREVENT IT? - Muhammad Retsa Rizaldi Mujayapura; Karim Suryadi; Sardin Sardin (Nurul Jadid University, 2021)
This article aims to examine the importance of information literacy and scientific literacy skills to prevent exposure to misinformation in the midst of the Covid-19 pandemic. Believing in misinformation encourages behaviour that is detrimental to individuals and groups due to anxiety, fear, uncertainty, and a lack of critical thinking skills. This study uses a qualitative approach with a systematic literature review (SLR) method. Through the SLR method, this article uses various sources of empirical research by collecting data and information to analyze elements in information literacy and scientific literacy that can identify misinformation. Information literacy is considered to be more useful in preventing belief in misinformation compared to the concepts of digital literacy, media literacy, and news literacy. Information literacy skills with information verification, and supported by scientific literacy with intellectual virtue, can recognize misinformation about COVID-19 so that it can prevent individuals from believing in misinformation that can result in errors of action. Scientific information literacy needs practical intervention to the public, one of which is through the role of educational institutions.